From the Bottom Up: Effective School Improvement in Dulangkou Junior Secondary School in China - Sun, Hechuan; Wang, Xiaodong (Profesorado, Revista de Currículum y Formación del Profesorado, 2011)
This paper unfolds the current educational reforming tendency and the effective school improvement in China. It presents a remarkable case study on how to change a failing rural school into an unbelievable effective and most successful one in Chinese basic education. It focuses on the instructional leadership perspective, particularly on the administration, managerial and instructional strategies that the school instructional leadership used to turnaround and to change a “bottom” school into a “top” effective one in China.